Transformation of the head-direction signal into a spatial code - Adrien Peyrache (Nature Portfolio, 2017)
A cognitive map of space must integrate allocentric cues such as head direction (HD) with various egocentric cues. Here the authors report that anterior thalamic (ADn) neurons encode a pure HD signal, while neurons in post-subiculum represent a conjunction of HD and egocentric cues such as body posture with respect to environment boundaries.